Jenis-Jenis Gulma yang Ditemukan di Perkebunan Karet (Hevea brasiliensis Roxb.) Desa Rimbo Datar Kabupaten 50 Kota Sumatera Barat - Hamida Febra Maya Sari; S S Budi Rahayu (Biogenesis: Jurnal Ilmiah Biologi, 2013)
Rubber is one of the agriculture commodity in Indonesia as resource of stock-exchange and permeating many labours. Weeds is one of the problem of which is often met in plantation conducting. Existence of weeds at rubber plantation (Hevea brasiliensis Roxb.) are rival to fundamental plants in exploiting mineral, water, light, degrading efficiency usage of manure, and bother tapping. This research aim is to know kinds of weed species in the plantation of Rubber (Hevea brasiliensis Roxb.).The plantation is located at the Rimbo Datar countryside, sub province of 50 Kota, West Sumatera. The method that used in this research is exploration, by taking of weeds sample, making in to herbarium and identification by using determination book.Pursuant to research got by 20 species which included in 14 familia. From these species can be grouped to become the grasses (Axonopus compressus P.B., Eleusine indica Gaertn, Imperata cylindrica, Cynodon dactylon Pers. and Paspalum vaginatum Berg.), seed grasses (Cyperus rotundus L., and Cyperus killingia) and the weeds that have wide leaf (Mikania cordata, Ageratum conyzoides L., Mimosa pudica L., Passiflora foetida L., Gleichenia linearis Clarke., Pityrogramma calomelanos, Blumea lacera, Cibotium barometz, Melastoma affine, Nephrolepis hirsutula, Lygodium flexuosa, Polygala paniculata L., and Melhania incana). Imperata cylindrica and Cibotium barometz which the most dominant species in that rubber plantation.Keywords: Rimbo Datar countryside, rubber plantation, weeds